2015
DOI: 10.1002/smll.201501034
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Codelivery of Doxorubicin and siRNA by pH‐Sensitive Nanoparticles for Therapy of Metastatic Lung Cancer

Abstract: A pulmonary codelivery system that can simultaneously deliver doxorubicin (DOX) and Bcl2 siRNA to the lungs provides a promising local treatment strategy for lung cancers. In this study, DOX is conjugated onto polyethylenimine (PEI) by using cis-aconitic anhydride (CA, a pH-sensitive linker) to obtain PEI-CA-DOX conjugates. The PEI-CA-DOX/siRNA complex nanoparticles are formed spontaneously via electrostatic interaction between cationic PEI-CA-DOX and anionic siRNA. The drug release experiment shows that DOX r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 46 publications
1
65
0
Order By: Relevance
“…Hematoxylin and eosin (H&E) staining analyses showed that cRGD‐PS‐DM1 nano‐prodrug did not induce obvious damage to the major organs of treated mice (Figure S4, Supporting Information), corroborating that this nano‐prodrug formulation has a low systemic toxicity. B16F10 melanoma is known as a highly aggressive malignancy . The high treatment efficacy and low side effects of cRGD‐PS‐DM1 nano‐prodrug in B16F10 tumor‐bearing mice suggests that this nanodrug platform has a great potential for cancer chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Hematoxylin and eosin (H&E) staining analyses showed that cRGD‐PS‐DM1 nano‐prodrug did not induce obvious damage to the major organs of treated mice (Figure S4, Supporting Information), corroborating that this nano‐prodrug formulation has a low systemic toxicity. B16F10 melanoma is known as a highly aggressive malignancy . The high treatment efficacy and low side effects of cRGD‐PS‐DM1 nano‐prodrug in B16F10 tumor‐bearing mice suggests that this nanodrug platform has a great potential for cancer chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Given that B16 murine melanoma cancer cells harbor favorable and selective propensity to metastasize to the lung, 62,63 we used this model to determine the anti-tumor effect of MoS 2 /GO by making best use of its preferential lung targeting capability. As shown in Supplementary Figure S9A, there was no significant difference in body weight among all groups, and no abnormal activities (for example, diet and moving) were observed for all mice, ruling out the occurrence of gross toxicity to mice treated with these materials.…”
Section: Preferential Lung Accumulation Of Mos 2 /Go Nanocompositesmentioning
confidence: 99%
“…siRNA expression plasmid pBabe-Super was chosen in this study, which directed the synthesis of small interfering RNAs in cells. The findings reveal that newly synthesized nucleocapsid, polymerase A (PA) and polymerase B1 (PB1) proteins are required for avian influenza virus transcription and replication and provide a basis for the development of small interfering RNAs as prophylaxis and therapy for avian influenza infection in birds and humans [24].…”
Section: Discussionmentioning
confidence: 99%